2016
DOI: 10.1177/1756287216663979
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib in the treatment of metastatic renal cell carcinoma

Abstract: Sunitinib is an oral multi-targeted tyrosine kinase inhibitor (TKI) that targets various receptors, including vascular endothelial growth factor receptors (VEGFRs). Sunitinib received approval in 2006 and became a standard treatment option in the first-line treatment of metastatic renal cell cancer (mRCC) after a phase III trial showed superiority compared with interferon alpha (IFN-α). Sunitinib has also shown activity in second-line treatment in several trials. Most of the combination trials with sunitinib w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 132 publications
0
37
0
1
Order By: Relevance
“…Sunitinib is a molecular targeted therapy drug used as the firstline chemotherapy agent for metastatic RCC [4] . Sunitinib works as a multi-targeted tyrosine-kinase inhibitor whose targets include vascular endothelial growth factor (VEGF) receptors, stem cell growth factor receptor (KIT), Platelet-derived growth factor receptor (PDGFR) and macrophage colony-stimulating factor receptor (MCSFR) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sunitinib is a molecular targeted therapy drug used as the firstline chemotherapy agent for metastatic RCC [4] . Sunitinib works as a multi-targeted tyrosine-kinase inhibitor whose targets include vascular endothelial growth factor (VEGF) receptors, stem cell growth factor receptor (KIT), Platelet-derived growth factor receptor (PDGFR) and macrophage colony-stimulating factor receptor (MCSFR) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that in pure PRCC2 biology, everolimus does show better chemopreventative effect than sunitinib. Two previous trials (ASPEN and ESPN) have attempted to compare between sunitinib and everolimus treatment in PRCCs (Armstrong et al, 2016;Schmid and Gore, 2016;Tannir et al, 2016). In both the ASPN and ESPN trials, no attempt was made to subtype the PRCC patients or distinguish between the treatment arms in the specific PRCC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of sunitinib with chemotherapy was not explored after phase I trials showing its poor safety profile [81]. Trials combining sunitinib with other therapies have also shown no improved efficacy, yet increased toxicity [82]. On the other hand, Sorafenib was also proven to have high clinical efficacy against mRCC, both as firstand second-line therapy [83].…”
Section: Rccmentioning
confidence: 99%